Kinerja SKPD Lingkup Pemerintah Kota Kupang dalam Pemberian Pelayanan Perijinan - Frits Fanggidae; Frans Nyong (Badan Penelitian dan Pengembangan Daerah Kota Kupang, 2017)
Public service is one government jobs which must be done. The achievement institution especially in public service is are of succes indicators indoing then job. Assessment for public service achievenment based on PERMEN PAN-RB number 38 year 2012 about guidance of performance assessment of public service unit includes nine components that is : vision, mission and motto, service standard and service announcement, system, procedure and mechanism, human resource, fool and infrastructure, hardling denuciation, society satisfaetion index, public service information system and productivity of targeting service achievement. Conceptually there are five principles that must be considered to reach the quality of service such as tangible, realiable, responsiveness, asurance and emphaty. The performance of permit service on Local Government Agencies of Kupang City Goverment, is measured by five superior service principles with nine performance assessment showed that the performance of Local Government Agencies of Kupang City Government, especially in permit service has variety range which can be shown from perfomance assessment or five quality principles service. It is proved that the performance of public service cannot be seen from one component or one aspect only but i is complex and multi dimensional. Thus the rising of permit service perormance must be done comprehensively, at least it includes three aspect such as human resource, fool and infrastructure and work system.